The utilization of innovation management to augment corporate competitiveness: A literature review - Arman, Feti; Nurraihan, Faiq (Junal Ilmu Manajemen, 2025)
This study aims to analyze the relationship between the implementation of innovation management and the enhancement of corporate competitiveness across various industrial sectors. By employing a literature review approach, this research collects and analyzes data from various relevant SINTA-accredited articles. The findings indicate that product innovation, marketing, and human resource management are key factors contributing to the success of innovation in improving competitiveness. Additionally, internal factors such as supportive leadership, an innovative organizational culture, and effective knowledge management have proven to be important in creating a conducive environment for innovation. On the other hand, technological support, collaboration with external parties, and strong business ethics also play a crucial role in the successful implementation of innovation management. This study concludes that to enhance competitiveness, companies need to integrate various aspects of innovation while considering both internal and external factors. Recommendations are provided for companies to continue investing in innovation, develop their human resources, and build strong collaborations with other stakeholders. This research is expected to offer deeper insights into effective innovation management strategies and their impact on corporate performance.